2022
DOI: 10.3390/nano12040579
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Fenton-like Degradation of Ciprofloxacin Using Corncob Biochar-Based Magnetic Iron–Copper Bimetallic Nanomaterial in Aqueous Solutions

Abstract: An economical corncob biochar-based magnetic iron–copper bimetallic nanomaterial (marked as MBC) was successfully synthesized and optimized through a co-precipitation and pyrolysis method. It was successfully used to activate H2O2 to remove ciprofloxacin (CIP) from aqueous solutions. This material had high catalytic activity and structural stability. Additionally, it had good magnetic properties, which can be easily separated from solutions. In MBC/H2O2, the removal efficiency of CIP was 93.6% within 360 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…It was observed that the removal efficiency of MB gradually decreased as the initial pollutant concentration increased. This decline in removal efficiency may be attributed to the occupation of active sites on the ZnFe 2 O 4 @BC catalyst at high MB concentrations [37] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the removal efficiency of MB gradually decreased as the initial pollutant concentration increased. This decline in removal efficiency may be attributed to the occupation of active sites on the ZnFe 2 O 4 @BC catalyst at high MB concentrations [37] …”
Section: Resultsmentioning
confidence: 99%
“…This decline in removal efficiency may be attributed to the occupation of active sites on the ZnFe 2 O 4 @BC catalyst at high MB concentrations. [37] The impact of H 2 O 2 concentration on MB degradation was investigated within the range of 5 mM to 11 mM, as shown in Figure 2g. The results indicated that the degradation efficiency of MB initially increased with higher H 2 O 2 concentration, followed by a decrease.…”
Section: Photo-catalytic Activitymentioning
confidence: 99%
“…29−31 The supporting effect of carbon, such as dispersion of magnetic nanoparticles and/or enriching pollutants to the interfacial reaction sites, has been focused in the previous studies. 32,33 Co-activation of H 2 O 2 using pyrogenic carbon and iron sources together provides a novel solution for the sustainable oxidation of organic pollutants, because pyrogenic carbon can mediate microbial reduction of Fe(III) 34−36 and may facilitate the regeneration of Fe(II) in Fenton reaction (eq 1). Thus, the enhanced oxidation efficiency of pollutants by coactivation of H 2 O 2 using biochar and aqueous iron (Fe(III) been observed in our previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a capable adsorbent of pollutant, , pyrogenic carbon can mediate electron transfer in redox reactions. For example, biochar alone can activate H 2 O 2 , and persulfates , to produce ROS for oxidation of pollutants. However, the yield of • OH from H 2 O 2 decomposition in the biochar-activated system was less than 10% while H 2 O and O 2 are the dominant products. , Thus, pyrogenic carbon was more often used as the supporting material of other active ingredients (e.g., iron nanoparticles) to enhance the performance of AOPs. The supporting effect of carbon, such as dispersion of magnetic nanoparticles and/or enriching pollutants to the interfacial reaction sites, has been focused in the previous studies. , Co-activation of H 2 O 2 using pyrogenic carbon and iron sources together provides a novel solution for the sustainable oxidation of organic pollutants, because pyrogenic carbon can mediate microbial reduction of Fe­(III) and may facilitate the regeneration of Fe­(II) in Fenton reaction (eq ). Thus, the enhanced oxidation efficiency of pollutants by coactivation of H 2 O 2 using biochar and aqueous iron (Fe­(III) or Fe­(II)) has been observed in our previous studies. , However, little is known about the performance of pyrogenic carbon on coactivation of H 2 O 2 with magnetite, although magnetite has been reported to be a reactive iron mineral to catalyze Fenton reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The most important applications of biochar concern soil amendment and agriculture [1][2][3] , but recently much has been achieved in the design of biochar-supported nanocatalysts for water treatment consisting in total mineralization of organic pollutants such as dyes and drugs 4,5 . Other applications concern the use of biochar as fillers in composite materials [6][7][8] , electrode materials 9,10 and for the developments of novel engineered biochar for the treatment of neglected tropical diseases (NTDs) 11,12 , to name but these applications.…”
Section: Introduction and Scope Of The Reviewmentioning
confidence: 99%